(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article explores the role of digital technologies in reducing enterprise logistics costs. Particular attention is given to the implementation of artificial intelligence (AI), the Internet of Things (IoT), blockchain, automation, and robotics in logistics processes. The study analyzes how these technologies improve warehouse operations, transportation management, inventory control, and documentation workflows. Examples from leading companies such as Amazon, DHL, and Maersk illustrate the effectiveness of digital integration. The findings show that digitalization enhances process transparency, forecasting accuracy, and operational efficiency while minimizing human errors and losses. The article concludes that digital transformation is a key strategic factor for improving competitiveness in modern logistics systems.